A Dynamic Model of Embeddedness in Digital Infrastructures - Fürstenau, Daniel; Baiyere, Abayomi; Kliewer, Natalia (Information Systems Research, 2019)
Digital infrastructures result from individual yet interdependent systems evolving in relation to each other. This paper identifies three processes by which individual systems become embedded into digital infrastructures. The first is a parallel process, whereby systems become embedded independently of each other. The second is a competitive process, whereby systems compete for resources and attention and one system usually thrives while the other system loses importance. The third is a spanning process characterizing a situation of boundary-spanning between distinct parts of a digital infrastructure. The three processes, synthesized into a dynamic model of digital infrastructure embeddedness, offer clarity to the question how digital infrastructures evolve. They also provide insight into the emergence of three forms of digital infrastructures: silofied, regenerated, and unified. Reflecting an interconnection view, our research further facilitates an understanding of infrastructure inertia and its associated consequence. Criticality traps should be avoided by considering the right timing for system replacement in the light of growing embeddedness over time.